"Five‐point eight‐line" anatomic flap design for precise hemitongue reconstruction. Issue 5 (17th December 2018) - Fan, Song; Li, Qun‐Xing; Zhang, Han‐Qing; Liang, Mao‐Jin; Tian, Tian; Wang, You‐Yuan; Lin, Zhao‐Yu; Chen, Wei‐Xiong; Pan, Guo‐Kai; Ahn, Michael Ho‐Young; He, Lile; Sun, Sheng; et al.
Abstract: Background: Reconstruction of hemiglossectomy defects requires careful flap design to avoid adverse functional and aesthetic outcomes. Methods: Hemitongue specimens were obtained from minipigs to study the three‐dimensional anatomy and to define anatomic landmarks for precise measurements of flap requirement. The concept developed in animal models was then applied to hemiglossectomy reconstruction in clinical practice. Sixty‐one patients were randomly enrolled into the following two groups: a "five‐point eight‐line segment" (FIPELS) flap design group (28 patients) and a conventional group (33 patients). Functional and aesthetic outcomes were compared between the two groups. Results: All flaps designed with the FIPELS technique matched the hemiglossectomy defects without the need for flap trimming, thus reducing the operating time ( P  = .03). Swallowing functions, speech intelligibility, and aesthetic outcomes were superior in the FIPELS group than that in the conventional group ( P  < .05). Conclusions: The FIPELS flap design for hemiglossectomy reconstruction yields improved functional and aesthetic outcomes compared to a conventional flap design.